From disagreement to rupture: the Soviet-Albanian conflict of 1960-1961 - K. K. Khudoley (Vestnik MGIMO-Universiteta)
The Soviet-Albanian conflict epitomized centrifugal tendencies within the global socialist system. This article draws on a diverse array of sources, including previously unpublished materials, such as documents from the State Archive of the Russian Federation and the Archive of Foreign Policy of the Russian Federation, as well as memoirs of key leaders (N. Khrushchev, E. Hoxha, R. Alia), and various official records. Notably, the TASS bureau in Tirana provided invaluable insights, collaborating with diplomats and journalists from other socialist nations to produce analytical reports, some of which were directed to the upper echelons of the CPSU. The article explores the evolution of discord between Moscow and Tirana, its culmination in open conflict, and the subsequent severance of party and state relations. Key findings include: 1) The conflict's primary catalysts were the divergent socialist models adopted by the USSR and Albania, coupled with the disparity in interests between the superpower and the bloc's smallest member; 2) The PLA's reluctance to conform to Soviet-style reforms was construed in Moscow as a challenge to the CPSU's hegemony within the global communist movement, while the PLA leadership viewed them as encroachments on its authority; 3) Disagreements pervaded all spheres, with ideology assuming heightened significance compared to conflicts with Yugoslavia; 4) External influences on the conflict's trajectory were marginal, with developments driven by internal dynamics, including Tirana's increasing alienation from the CPSU and the catalytic effect of deteriorating Soviet-Chinese relations; Western powers monitored events closely but refrained from direct intervention; 5) While objective factors underpinned the Soviet-Albanian discord, subjective elements were of secondary importance, yet pivotal in precipitating the conflict's acrimonious turn.